Unfulfilled Dreams? The Financial Situation of Workers in Paris and the Department of Loir-et-Cher between 1789 and 1795 - Derejski, Krzysztof (Studia Historiae Oeconomicae, 2024)
The convening of the Estates General in France in 1789 raised high hopes in French society for change. The economic demands written down in the ledgers of complaints, such as the abolition of the guild system, the unification of taxes and their more equitable distribution, the abolition of customs duties and fees within the kingdom, can be categorized as inclusive economic institutions. Their introduction in France during the Revolution was expected to translate into an improvement in the financial conditions of the population. The purpose of this article is to present the changing financial situation of workers in Paris and the department of Loir-et-Cher between 1789 and 1795 in the context of the aforementioned institutions. Data from a survey of prices and wages conducted at the behest of the Committee of Public Safety, Paris police reports of 1795 and depreciation tables were used to show the change in the financial position of working families during the French Revolution. Demands from the ledgers of complaints against the Estates General of 1789 were used to determine the title workers' "dreams." Assessing the change in the financial situation of workers required calculations that took into account, among other things, the size of the average working family's demand for foodstuffs or the change in France regarding the number of working days per year after the elimination of the old holidays and the introduction of the republican calendar. During the period under review, the financial situation of workers in the Loir-et-Cher department worsened due to high inflation – turning at times into hyperinflation – despite the implementation of most of the demands of the ledgers of complaints by the revolutionary authorities. In the case of Paris, the assessment is not so clear-cut. Thanks to the rationing of bread and meat in the capital, and their sale at a discounted price by the authorities, the living conditions of working families in 1795 were better or comparable to those at the beginning of the revolution. The article sheds new light on the changing financial situation of workers in Paris and the department of Loir-et-Cher in the context of the implementation of workers' demands recorded during the revolution in the ledgers of complaints to the Estates General of 1789, thus filling a gap in historiography.